Students’ Perceptions of Using U-Dictionary as A Media in Translation At MTSN 17 Jakarta - Barokah, Okta Muji; Burhayani (Syntax Literate, 2023)
This study aims to understand students' perceptions of using U-Dictionary as a support tool in the translation process. The study was conducted using qualitative methods and involved students from MTsN 17 Jakarta, who used U-Dictionary in translation activities. Data were collected by translating a descriptive text and collecting data using a questionnaire about the process of using U-Dictionary in translation work of Grade 9 students. Analysis results show that students at MTsN 17 Jakarta has a generally positive view of usage. of U-Dictionary as a means of translation, noting its advantages in understanding and finding equivalents. However, some challenges were also identified, including limitations in dictionary functionality and language capabilities. These results provide valuable insights into the effectiveness and usefulness of U-Dictionary as a translation aid, as well as its potential impact on improving translation performance. of students. This study recommends further development of dictionary technology and better integration into educational programs to support the use of U-Dictionary as an effective means of learning translation.